Stealing the Goose: Copyright and learning - McGreal, Rory (International Review of Research in Open and Distributed Learning, 2004)
The Internet is the world's largest knowledge common and the information source of first resort. Much of this information is open and freely available. However, there are organizations and companies today that are trying to close off the Internet commons and make it proprietary. These are the “copyright controllers.” The preservation of the commons and expanding access to digital content and applications are very important for distance educators. The educational exemptions for “fair use” in the United States and “fair dealing” in the Commonwealth countries are integral to any understanding of copyright, which was instituted for the dissemination of knowledge, and not, as is commonly believed, to protect the rights of the copyright owners. Copyright law was expressly introduced to limit their rights. Yet, these controllers are successfully turning a “copy” right into a property right. The traditional rights of learning institutions are being taken away. The balance for researchers should be restored. Research and learning must be allowed the broad interpretation that was intended in the original laws.